Kajian Pengeringan Jahe (Zingiber Officinale Rosc) berdasarkan Perubahan Geometrik dan Warna menggunakan Metode Image Analysis (Study of Dried Ginger (Zingiber Officinale Rosc) based on Changes in Geometric and Color using Image Analysis): Study of Dried Ginger (Zingiber officinale Rosc)Based on Changes in Geometric and Color using Image Analysis - Devi Risdianti; Murad Murad; Guyup Mahardhian Dwi Putra (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Purpose of this study was to determine change in geometric and color during the drying process using image analysis method. Method used in this study was experimental method. Tools and materials used were ginger, image acquisition box, digital cameras, and computers. Measured parameters included temperature, moisture content, mass of material, geometry and color changes. Results from this study showed that the lowest value of material mass was 1.91 gr of the lowest shelf and 3.21 gr of the upper shelf which directly proportional to the reduction of material moisture content at lowest shelf by 5.66%, due to the heating source placed near the shelf, therefore it will directly heat the material. While the highest value was showed by the highest shelf material of 13.93% moisture content. Actual measurement of surface shrinkage showed declining during 8-hour drying and result from image analysis ranged from 37,548 to 17,201 pixels, 27.77 cm2 to 10.07 cm2by using trapezoidal numerical integration of the highest shelf, and 27.3 cm2 to 10.37 cm2 by using Simpson methods. Based on this study, image analysis can be used to measure ginger color changes from yellowish white to brownish yellow and measure surfaces shrinkage.